Challenges and opportunities of Implementing Mother Tongue- Based Multilingual Education in Assam (International Journal of Food and Nutritional Sciences, 2022)
Mishing, is the language of the second largest cultural community in Assam after the Bodos and is taught as a language subject in the 3rd and 4th standards in 230 schools in the districts of Dhemaji, North Lakhimpur, Sonitpur on the upper bank and Tinsukia, Dibrugarh, Jorhat and Golaghat on the lower bank of the Brahmaputra River of Assam. This article briefly discusses the opportunities and challenges of teaching Mishing as a language subject in schools and introducing it as a medium of instruction.